Investigation of the Effect of Non-Flat Surfaces on the Performance of Perforated Acoustic Absorber - HASHEMI, Zahra; FAHIM, Ali; MONAZZAM, Mohammad Reza (Archives of Acoustics, 2023)
In order to investigate the effect of the surface shape on the performance of perforated panels, three non-flat shapes were considered for perforated panel with their absorption performance compared with the usual shape of the (flat) perforated panel. In order to simulate the absorption coefficient of a non-flat perforated panel, the finite element method was implemented by the COMSOL 5.3a software in the frequency domain. Numerical simulation results revealed that all the shapes defined in this paper improve the absorption coefficient at the mid and high frequencies. A and B shapes had a higher performance at frequencies above 800 Hz compared to the flat shape. Also, shape C had a relative superiority at all frequencies (1–2000 Hz) compared to the reference shape; this superiority is completely clear at frequencies above 800 Hz. The maximum absorption coefficient occurred within the 400–750 Hz range. After determining the best shape in terms of absorption coefficient (shape C), a perforated panel of 10 m2 using fiberglass fibers and desired structural properties was built, and then it was also subjected to a statistical absorption coefficient test in the reverberation chamber according to the standard. The results of the statistical absorption coefficient measurement showed that the highest absorption coefficient was 0.77 at the frequency of 160 Hz. Also, to compare the experimental and numerical results, these conditions were implemented in a numerical environment and the statistical absorption coefficient was calculated according to the existing relationships. A comparison of the numerical and laboratory results revealed acceptable agreement for these two methods in most frequency spectra, where the numerical method was able to predict this quantity with good accuracy.